Early Global Interconnectivity across the Indian Ocean World, Volume I
XXI, 401 p. 52 illus., 37 illus. in color.
Keywords: This volume investigates the emergence and spread of maritime commerce and interconnectivity across the Indian Ocean World—the world’s first “global economy”—from a longue durée perspective. Spanning from antiquity to the nineteenth century, these essays move beyond the usual focus on geographical sub-regions or thematic aspects to foreground inter- and trans-regional connections. Analyzing multi-lingual records and recent archaeological findings, volume I examines mercantile networks, the role of merchants, routes, and commodities, as well as diasporas and port cities.